2020
DOI: 10.1099/mgen.0.000385
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequence analysis of environmental Escherichia coli from the faeces of straw-necked ibis (Threskiornis spinicollis) nesting on inland wetlands

Abstract: Wildlife, and birds in particular, play an increasingly recognized role in the evolution and transmission of Escherichia coli that pose a threat to humans. To characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The long-read assembly of E. coli strain IBS28 resolved two contigs, a 4 934 027 bp chromosome, plus the ICE pIBS28_1, as described previously [ 43 ]. Automated annotation identified 4877 open reading frames (ORFs) and 112 RNA coding sequences in the chromosome.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The long-read assembly of E. coli strain IBS28 resolved two contigs, a 4 934 027 bp chromosome, plus the ICE pIBS28_1, as described previously [ 43 ]. Automated annotation identified 4877 open reading frames (ORFs) and 112 RNA coding sequences in the chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…Here we characterized an environmentally associated E. coli ST58 (ISB28) from the straw-necked ibis. Our initial analysis utilizing short-read whole-genome data indicated that IBS28 was closely related to a series of strains from North America dating back to 1988, and we detected several virulence genes plus an unusual chromosomal IS 6 family element [ 43 ]. Members of the IS 6 family are frequently involved in the dissemination of antimicrobial resistance genes [ 53 ], although none were detected within the strain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations